An overview to unmanned aerial vehicles from perspectives of quality and safety management in aviation - ŞENVAR, ÖZLEM (My University, 2022)
Aviation is one of the pioneer industries of technology and military aviation has been a big contributor to the technological developments in the industry. The Unmanned Aerial Vehicles (UAVs) have been in the military domain for years; however, their civil applications are fairly new and rapidly expanding. Due to their capabilities and ease of handling, they have been utilized in various operations such as monitoring, surveillance, remote sensing and delivery. Although their engines and avionics have been improved, there have been still major challenges with UAVs in terms of reliability, safety and maintenance. Quality and safety management concepts are inevitable for civil aviation industry and liable to many regulations and standards. These concepts are not yet fully established for UAVs and the regulations and standards are still in progress. The objective of this study is to provide an overview to UAVs from perspectives of quality and safety management in aviation. Additionally, new trends, developments and research areas are discussed as well
Keywords: Unmanned aerial vehicle (UAV); Drone; Quality management; Safety management